CONSTRUCTION OF RAIN-CALLING RITUALS: A CASE STUDY OF THE OJHUNG TRADITION IN BATUPUTIH DAYA, MADURA - Moh Rodi; Raafi Herdiansyah Putra; Andri Rosadi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
The Ojhung tradition is a fighting art performed by two men in Batuputih using a whip in an open arena. In practice, this fighting art then transformed into a rain-calling ritual. This study aims to reveal the transformation of Ojhung from a fighting art into a rain-calling ritual, along with the meaning contain in it. This study employs a qualitative approach. The data will be analyzed using Clifford Geertz's interpretive theory. The results of the study indicate that Ojhung is a fighting art for Sumenep soldier training in the 12th century, led by the Singasari kingdom's dignitaries who were in Sumenep. When the Singasari dignitaries left Sumenep, Ojhung continued and developed into a rain-summoning ritual by the local people. In the process of interpretation of meaning, several elements are used, such as whips, music, offerings, time and place that represent their own symbolic meanings.